2012
DOI: 10.1038/leu.2012.256
|View full text |Cite
|
Sign up to set email alerts
|

Aurora kinases in childhood acute leukemia: the promise of aurora B as therapeutic target

Abstract: We investigated the effects of targeting the mitotic regulators aurora kinase A and B in pediatric acute lymphoblastic leukemia (ALL) and acute myeloid leukemia (AML). Aurora protein expression levels in pediatric ALL and AML patient samples were determined by western blot and reverse phase protein array. Both kinases were overexpressed in ALL and AML patients (P<0.0002), especially in E2A-PBX1-translocated ALL cases (P<0.002), compared with normal bone-marrow mononuclear cells. Aurora kinase expression was si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(47 citation statements)
references
References 32 publications
1
45
1
Order By: Relevance
“…However, PLK1 expression was relatively high in all cell lines (data not shown), probably due to their proliferative capacity, and factors like transfection efficiency and rate of protein knockdown differ between PLK1 in childhood acute lymphoblastic leukemia haematologica | 2013; 98 (10) 1543 We have previously shown that AURKB protein expression is up-regulated in pediatric ALL and correlates with sensitivity to an AURKB inhibitor. 31 It has been shown that PLK1 is required for activation of AURKB and vice versa, 41 but this does not explain the correlation between PLK1 and AURKB protein expression that we observed in ALL patients. Rather than a direct connection between the two, the cross-talk between PLK1 and AURKB and their shared functions in mitotic processes make it more likely that there is a common factor regulating the expression of PLK1, AURKB and possibly other proteins involved in the same pathway.…”
Section: Discussioncontrasting
confidence: 65%
See 4 more Smart Citations
“…However, PLK1 expression was relatively high in all cell lines (data not shown), probably due to their proliferative capacity, and factors like transfection efficiency and rate of protein knockdown differ between PLK1 in childhood acute lymphoblastic leukemia haematologica | 2013; 98 (10) 1543 We have previously shown that AURKB protein expression is up-regulated in pediatric ALL and correlates with sensitivity to an AURKB inhibitor. 31 It has been shown that PLK1 is required for activation of AURKB and vice versa, 41 but this does not explain the correlation between PLK1 and AURKB protein expression that we observed in ALL patients. Rather than a direct connection between the two, the cross-talk between PLK1 and AURKB and their shared functions in mitotic processes make it more likely that there is a common factor regulating the expression of PLK1, AURKB and possibly other proteins involved in the same pathway.…”
Section: Discussioncontrasting
confidence: 65%
“…HEK293T cells were transfected as described before 31 with psPAX2 (Addgene plasmid 12260) and pMD2.G (Addgene plasmid 12259), and a pLKO.1 Mission® vector (Sigma-Aldrich, Zwijndrecht, The Netherlands) containing a puromycin selection marker and a short hairpin RNA (shRNA) against PLK1 (TRCN0000121222) or eGFP (SHC005) as a non-targeting control (NTC). After 24 h, transduced cells were selected on puromycin (Sigma-Aldrich).…”
Section: Lentiviral Infectionmentioning
confidence: 99%
See 3 more Smart Citations